Cardiac Tumors: Diagnosis, Prognosis, and Treatment - Bussani, Rossana; Castrichini, Matteo; Restivo, Luca; Fabris, Enrico; Porcari, Aldostefano; Ferro, Federico; Pivetta, Alberto; Korcova, Renata; Cappelletto, Chiara; Manca, Paolo; Nuzzi, Vincenzo; Bessi, Riccardo; et al. (Current cardiology reports, 2020)
Purpose of Review Cardiac masses frequently present significant diagnostic and therapeutic clinical challenges and encompass a broad set of lesions that can be either neoplastic or non-neoplastic. We sought to provide an overview of cardiac tumors using a cardiac chamber prevalence approach and providing epidemiology, imaging, histopathology, diagnostic workup, treatment, and prognoses of cardiac tumors. Recent Findings Cardiac tumors are rare but remain an important component of cardio-oncology practice. Over the past decade, the advances in imaging techniques have enabled a noninvasive diagnosis in many cases. Indeed, imaging modalities such as cardiac magnetic resonance, computed tomography, and positron emission tomography are important tools for diagnosing and characterizing the lesions. Although an epidemiological and multimodality imaging approach is useful, the definite diagnosis requires histologic examination in challenging scenarios, and histopathological characterization remains the diagnostic gold standard. Summary A comprehensive clinical and multimodality imaging evaluation of cardiac tumors is fundamental to obtain a proper differential diagnosis, but histopathology is necessary to reach the final diagnosis and subsequent clinical management.